Edukasi Urgensi Merek Kolektif dalam Penguatan UMKM Desa Nglanggeran - Fakultas Hukum Universitas Negeri Surabaya; Mieke Yustia Ayu Ratna Sari; Budi Hermono; Cita Yustisia Serfiyani; Eny Sulistyowati; Badriyatul Muniroh; Dhiezayu Alifia Idzihaar; Syaufi Al Amien; Karsito Sidauruk (Jurnal Darma Loka, 2025)
MSMEs play a vital role in the rural economy but often lack the legal awareness to protect their intellectual property. This community service initiative addressed the limited understanding of branding and collective trademark registration among MSMEs in Nglanggeran Village, Gunung Kidul, a key barrier to their market competitiveness. Using a participatory approach—through observation, focus group discussions, and interviews with MSME actors and village officials—the program provided outreach and capacity-building on the strategic importance of collective trademarks. Findings revealed that although MSMEs recognized branding's value, none had registered a collective trademark, citing limited information, financial constraints, and technical complexity as main barriers. The activity significantly increased participants’ understanding of the legal protection and economic benefits of collective trademarks and clarified distinctions between individual and collective marks. This awareness is a fundamental step toward legal empowerment. We recommend that local government and relevant institutions provide structured mentoring to facilitate registration. Strengthening MSMEs through collective trademarks is crucial for enhancing product differentiation, preventing unfair competition, and promoting sustainable local economic development.